An eco‐friendly method based on the self‐glue effect of keratins for preparing Fe3O4‐coated wool. Issue 39 (12th March 2020) - Zhao, Zhenyun; Song, Chi; Zhou, Jing; Hu, Ruimin; Xiao, Hang; Liu, Yiping; Lu, Ming
Abstract: Although coating technology and in‐situ synthesis have been widely applied to produce Fe3 O4 NPs‐containing composite materials, there still exist potential risks to the environment. Herein, an eco‐friendly preparation of Fe3 O4 nanoparticles (FNPs)‐coated wool felt is proposed based on the self‐glue effect of wool keratins in the NaHSO3 /urea solution. It avoids the use of coating agents, and also the commercially available FNPs are directly utilized as raw materials, both making the residual FNPs completely recyclable. The resulting FNPs‐coated wool felt shows high magnetization (23.54 emu g −1 ) and excellent microwave‐assisted heating properties (the temperature rise is about 40°C after 10 min). The results of EDS‐SEM (energy dispersive spectrometer‐scanning electron microscope), loud amount (%), crease recovery angle (CRA), Fourier transform infrared (FTIR) spectrometer and X‐ray diffraction (XRD) prove that the dramatical swelling and the recoagulation of superficial keratins of wool fibers are the mechanism of the self‐glue effect. Abstract :